Characterization of solid waste and design of a manual landfill for the district La Yarada Los Palos - Lazo Ramos, Richard Sabino (2020)
The study of the characterization of solid waste was carried out in the district La Yarada -Los Palos, Tacna Province, in order to analyze the home and non-domicile waste of homes, markets, schools, shops, hardware stores and curators. The methodology described by the Ministry of the Environment (2018) was used to determine the quantity and characteristics of solid waste by random sampling. The per capita generation of household solid waste was 0.470 kg/hab-day, in the physical composition, organic matter was found in greater quantity was 56.77 %, the average uncompacted density was 224,682 kg/m3 and the compacted 305,664 kg/m3. In terms of non-home waste, it was determined that educational institutions generate more solid waste at 38.47%, followed by grocery stores with 28.53%, fruit shops with 8.60%, restaurants 7.21% and places with 4.10%. With the information obtained, the manual landfill was designed by applying the Ministry of the Environment's Manual Sanitary Design, Construction, Operation, Maintenance and Closure Guide consisting of nine 2,659.2 m3 ditches of solid waste as a useful design volume with a 10-year projection for the 24552.7 m3. With cells 2.4 m high, upper length (ls) 60 m upper width (as) 30 m upper area 825 m2 trench slope (H) 1, trench slope (V) 1, lower length (li) 55.2 m, lower width (ai) 25.2 m and lower area (Ai) 1391.04 m2.